Growth, red blood cells, and gill alterations of red pacu (Piaractus brachypomus) fingerlings by chronic exposure to different total suspended solids in biofloc. Issue 3 (18th July 2021) - Angeles‐Escobar, Beatriz Elena; da Silva, Suzianny Maria Bezerra Cabral; Severi, William
Abstract: Chronic exposure to high biofloc total suspended solids (TSS) could affect growth, red blood cells, and generate gill alterations in fish. Red pacu, Piaractus brachypomus, fry (2.7 ± 0.5 g weight) were exposed to different biofloc TSS concentrations with low (T1: 200–300), and medium (T2: 400–600 mg/L) levels and compared to a treatment control (TC) without solids during a 45‐day period in 50 L experimental units (in quadruplicate). Water quality, productive parameters, red blood cell values, and gill histopathological alteration index (HAI) were assessed. Red pacu reached higher final biomass (11.34 ± 0.73 kg/m 3 ), better growth (DWG = 0.30 ± 0.03 g/day) and food conversion rate (1.05 ± 0.02) in TC than in biofloc treatments ( p < .05). T2 had higher RBC count, and lower hemoglobin, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration ( p < .05) than T1 and TC. The histological sections of TC gills showed monogenean parasites in low quantity; thus, the HAI value was similar among treatments and corresponded to low to medium gill damage. Growth, red blood cell values, and gill morphology of red pacu fingerlings were affected by moderate (400–600 mg/L) chronic exposure to TSS concentration in biofloc.